2009
DOI: 10.1007/s11094-009-0220-4
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the antioxidant and antihemolytic activity of quinoline derivatives in a model of oxidative damage to erythrocyte membranes

Abstract: New benzo-substituted 4-(aminophenylamino)-2-methylquinolines, 3-substituted 4-hydroxy(chloro and mercapto)quinolines, and thienoquinolines were synthesized. A model system based on oxidative damage to erythrocyte membranes induced by the combined actions of hydrogen peroxide and ionizing radiation was used to study the antihemolytic effects of these compounds as a means of assessing their antiradical/antioxidant properties. In the absence of x-rays, substances of the 3-substituted 4-hydroxy(chloro and mercapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Since the experiments conducted so far revealed that the ligands and its Cu(II) complexes exhibit good DNA and protein binding affinity, it is considered worthwhile to study the antioxidant activity of these compounds. The antioxidant properties of quinoline derivatives have attracted a lot of interest and have been extensively investigated, mainly in the in vitro systems. , The radical scavenging activities of our compounds along with standards such as butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) in a cell free system have been examined with reference to hydroxyl radicals (OH • ), DPPH radicals (DPPH • ), nitric oxide (NO), and superoxide anion radicals (O 2 –• ), and their corresponding IC 50 values have been tabulated in Table . It is to be noted that no significant radical scavenging activities were observed in all of the experiments carried out with CuCl 2 and Cu(NO 3 ) 2 , even up to 1.0 mmol of concentration under the same experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Since the experiments conducted so far revealed that the ligands and its Cu(II) complexes exhibit good DNA and protein binding affinity, it is considered worthwhile to study the antioxidant activity of these compounds. The antioxidant properties of quinoline derivatives have attracted a lot of interest and have been extensively investigated, mainly in the in vitro systems. , The radical scavenging activities of our compounds along with standards such as butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) in a cell free system have been examined with reference to hydroxyl radicals (OH • ), DPPH radicals (DPPH • ), nitric oxide (NO), and superoxide anion radicals (O 2 –• ), and their corresponding IC 50 values have been tabulated in Table . It is to be noted that no significant radical scavenging activities were observed in all of the experiments carried out with CuCl 2 and Cu(NO 3 ) 2 , even up to 1.0 mmol of concentration under the same experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, quinolines are considered as an interesting group of compounds, many of which have widespread pharmacologicalactions such as anti-microbial, [1][2][3][4] anti-inflammatory, [5][6][7][8] antitubercular, [9][10][11][12] anti-convulsant, [13] antihypertensive, [14,15] antioxidant, [16][17][18][19] and anticancer [20] activities. Nitrones can release nitric oxide in larger amounts compared to corresponding oximes.…”
mentioning
confidence: 99%
“…actions such as anti-microbial, [1][2][3][4] anti-inflammatory, [5][6][7][8] antitubercular, [9][10][11][12] anti-convulsant, [13] antihypertensive, [14,15] antioxidant, [16][17][18][19] and anticancer [20] activities. Several mechanisms can explain the anticancer effect of quinoline derivatives including: topoisomerase inhibition, [21][22][23] DNA intercalation, [24] protein kinases inhibition, [25][26][27] tubulin polymerase inhibition, [28][29][30][31] and induction of apoptosis.…”
mentioning
confidence: 99%
“…The quality of life of TB patients towards the 6th month seems to increase sharply along with the course of their illness towards recovery. The critical time for TB patients is in the 2nd month of treatment as a qualitative study on pulmonary tuberculosis patients at BP4 Tegal conducted by Nugroho (Nugroho, 2011) concluded that the underlying factor for dropping out of TB patients is treatment after the 2 nd month of treatment where the symptoms disappear and the patient feels get well. This condition can encourage patients to stop treatment.…”
Section: Discussionmentioning
confidence: 99%